Viaje por los cuerpos, el gonzo “carnal” de Gabriela Wiener (Altre Modernità, 2013)
(Gabriela Wiener, Sexografías, Barcelona, Melusina,2008, 214 pp. ISBN 978-849-661-453-6)(Gabriela Wiener, Nueve Lunas, Barcelona, Mondadori,2009, 158 pp. ISBN 978-843-972-203-8)